2018
DOI: 10.1038/s41419-017-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell adhesion molecule overexpression regulates epithelial-mesenchymal transition, stemness and metastasis of nasopharyngeal carcinoma cells via the PTEN/AKT/mTOR pathway

Abstract: Epithelial cell adhesion molecule (EpCAM) is known to be highly expressed in a variety of epithelial carcinomas, and it is involved in cell adhesion and proliferation. However, its expression profile and biological function in nasopharyngeal carcinoma (NPC) remains unclear. In this study, higher expression of EpCAM was found in NPC samples compared with non-cancer nasopharyngeal mucosa by qRT-PCR. Additionally, immunohistochemistry (IHC) analysis of NPC specimens from 64 cases showed that high EpCAM expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 43 publications
6
82
0
Order By: Relevance
“…The ability of EpEX to act as a ligand for EGFR is in line with the fact that EpCAM N-terminal domain (a region that constitutes the solubilized EpEX) contains the EGF-like motif, thus possibly enabling it to interact and bind to EGFR. Moreover, EpCAM has also been reported to promote tumourigenesis in prostate [63,111] and nasopharyngeal cancer [112] by modulating the activity of PI3K/AKT/mTOR pathway. These studies, however, did not further investigate whether the modulation of the PI3K/AKT/mTOR pathway was achieved via the soluble EpEX or cytoplasmic EpICD.…”
Section: Epcam Downstream Targets In Cancermentioning
confidence: 99%
“…The ability of EpEX to act as a ligand for EGFR is in line with the fact that EpCAM N-terminal domain (a region that constitutes the solubilized EpEX) contains the EGF-like motif, thus possibly enabling it to interact and bind to EGFR. Moreover, EpCAM has also been reported to promote tumourigenesis in prostate [63,111] and nasopharyngeal cancer [112] by modulating the activity of PI3K/AKT/mTOR pathway. These studies, however, did not further investigate whether the modulation of the PI3K/AKT/mTOR pathway was achieved via the soluble EpEX or cytoplasmic EpICD.…”
Section: Epcam Downstream Targets In Cancermentioning
confidence: 99%
“…A study by Maetzel et al showed that EpCAM intracellular domains form a complex with β-catenin and LEF-1 which activates the transcriptions of genes such as c-Myc and cyclins A and E. Its overexpression increased the phosphorylation of AKT, mTOR, p70S6K and 4EBP1 as well as decreased PTEN expression. EpCAM regulates EMT and metastasis in vivo [127] [128]. The study of Fong et al revealed that ESA was overexpressed in PC and that it was related to shorter survival of patients with advanced PC.…”
Section: Esamentioning
confidence: 99%
“…The association of EMT and HCC has also been reported in several clinical studies. A study of 123 HCC patient samples reported that the majority of clinically aggressive HCC samples had decreased E-cadherin expression, a marker of EMT status [91] . In addition, the study also reported that EMT transcription factors Snail and Twist were associated with poor prognosis in HCC with increased invasive and migratory potential [91] .…”
Section: Role Of Emt In Immune Checkpoint Blockade Therapymentioning
confidence: 99%